EFFECTS OF FOREIGN DIRECT INVESTMENT ON TURKEY-EU28 INTRA-INDUSTRY TRADE - (:unkn) unknown (My University, 2019)
This study aims to examine the distribution, progress and determinants of total (IIT), horizontal(HIIT) and vertical intra-industry trade (VIIT) between Turkey and EU28 and impact of foreigndirect investment on IIT in 2005-2016 period. According to empirical findings, although the shareof IIT in Turkey’s trade shows an increase, trade structure is mainly inter-industry. Results showthat, there is a transition from one way trade intensive structure to a structure that low qualityVIIT gains importance. When, Turkey’s total IIT with EU28 is compared with the World and nonEU28 economies, it is seen that one-way trade and low quality VIIT is higher; high quality VIIT andHIIT are at lower levels. In the model, it is confirmed that, IIT is in a positive relationship withmarket size, commerical proximity, trade openness and in a negative relationship with level ofeconomic development. Foreign direct investment affects the low quality VIIT negatively and highquality VIIT positively; in other IIT models there is no significant statistical effect.